-2(x-5)-(16-x)=4(2x-1)+7

Simple and best practice solution for -2(x-5)-(16-x)=4(2x-1)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-5)-(16-x)=4(2x-1)+7 equation:



-2(x-5)-(16-x)=4(2x-1)+7
We move all terms to the left:
-2(x-5)-(16-x)-(4(2x-1)+7)=0
We add all the numbers together, and all the variables
-2(x-5)-(-1x+16)-(4(2x-1)+7)=0
We multiply parentheses
-2x-(-1x+16)-(4(2x-1)+7)+10=0
We get rid of parentheses
-2x+1x-(4(2x-1)+7)-16+10=0
We calculate terms in parentheses: -(4(2x-1)+7), so:
4(2x-1)+7
We multiply parentheses
8x-4+7
We add all the numbers together, and all the variables
8x+3
Back to the equation:
-(8x+3)
We add all the numbers together, and all the variables
-1x-(8x+3)-6=0
We get rid of parentheses
-1x-8x-3-6=0
We add all the numbers together, and all the variables
-9x-9=0
We move all terms containing x to the left, all other terms to the right
-9x=9
x=9/-9
x=-1

You can always share this solution

See similar equations:

| (3x-8)=(-2x-1) | | 12+p-8=6 | | Y=2(1/5y)-15 | | Y=5(1/5y) | | 10–70+2x=10 | | 3x-16+2x=4x+15 | | 5x+51+4x+19=180 | | 7/z+1/3=-5/6 | | 12+p-2=12 | | 18-4u=5u | | -10(2.5+0.7y)+7y=-25 | | 9x-6=2(2x+3)-5(4-x) | | 5(2x-2)+4=-8-(-3x-2) | | 4x-(1-7x)=5 | | -(x+5)-2(x-6)=-3(x-1) | | 0.2*x+0.4=-0.5*x+6 | | x-5=3+x-8 | | 3x+12=6+x | | -4(2.5+0.7y)-2y=14 | | 14y+2y-6=3y+8 | | 2x+I=7 | | 7+2x+4=3x-6 | | 5x^2+21x=?10x?6 | | 7+10x=-2(-5x-8)-7 | | X+x^2=78 | | B=4/3(j-36) | | v=5108551 | | 84=-12+x | | 3(1+5x)=8x+3 | | -6-8x=-2+4(x-4) | | -4(-3.5+-0.5y)-2y=14 | | 1+4(x-8)=4x-31 |

Equations solver categories